Scientific Analysis of Rose Essential Oils: Viewed from Various Perspectives - Deni Ainur Rokhim; Fadhila Agustina S; Kafita Krisnatul Islamiyah; Annida Elfiana Citra Ardianty; Sutrisno Sutrisno; Siti Marfuah (Program Studi Kimia, Fakultas Teknik, Universitas Samudra, 2022)
The use of essential oils in the world each year has increased with the increasing development of modern industries such as the perfume industry, cosmetics, food, aroma therapy and medicine. Essential oils or also known as etheric oils are a large group of vegetable oils in the form of viscous liquids at room temperature but volatile so that they give a distinctive aroma. Some components of essential oils are hydrocarbon compounds (hydrogen-carbon) and oxygen. One source of essential oils can be obtained from rose extract. This study aims to analyze the physical, chemical, and beneficial properties of several components of the rose essential oil. This research approach uses a qualitative approach with a literature study method, then the data were analyzed using descriptive analysis. The results obtained conclude that the essential oil content in roses with the highest percentage is n-nonadekane, -phenylethylacetate, phenylethylalcohol, and 2-Isopropyl-5-methyl-9-methylene-bicyclo-1-decene, -Fernesene, and -cadinene. From these structures there are 2 types of hybrid orbitals, namely sp3 and sp2, when viewed from the type of bond π and σ; whereas if viewed from the isomerism, these structures have skeletal, functional groups, and optical isomers. Some of the constituents in the volatile oil components can be reacted (nucleophilic addition with HCl and electrophilic with bromine). The existence of these differences causes the chemical and physical properties of the structure of the essential oil content to vary according to their usefulness.